Segmental Tissue Speckle Tracking Predicts the Stenosis Severity in Patients With Coronary Artery Disease - Chaichuum, Srisakul; Chiang, Shuo-Ju; Daimon, Masao; Chang, Su-Chen; Chan, Chih-Lin; Hsu, Chu-Ying; Chen, Hsiang-Ho; Tseng, Ching-Li (Frontiers in Cardiovascular Medicine, 2022)
Objective: Two-dimensional speckle tracking echocardiography (2D-STE) has been used as a diagnostic tool for coronary artery disease (CAD). However, whether vessel supplied myocardial strain and strain rate (SR) predict the severity of coronary artery stenosis in patients with CAD is unknown. This study aimed to investigate correlation of cardiac mechanical parameters in tissue speckle tracking measurements with coronary artery stenosis diagnosed by cardiac catheterization in patients with clinically diagnosed CAD. Methods and Results: Among 59 patients analyzed, 170 vessels were evaluated by coronary angiography and the corresponding echocardiography to quantify left ventricular myocardial strain and SR. The average longitudinal strain and SR of the segmental myocardium supplied by each coronary artery were calculated to achieve vessel myocardium strain (VMS) and strain rate (VMSR). The VMS and VMSR at each of four severity levels of stenosis showed significant differences among groups (p = 0.016, and p < 0.001, respectively). The strain and SR in vessels with very severe stenosis (≥75%, group IV; n=29), 13.9 ± 4.3, and 0.9 ± 0.3, respectively, were significantly smaller than those of vessels with mild stenosis (≤25%, group I; n=88, 16.9 ± 4.9, p = 0.023, and 1.2 ± 0.3, p = 0.001, respectively. The SR in vessels with moderate stenosis (26%-49%, group II; n=37), 1.0 ± 0.2, was significantly smaller than that in vessels with mild stenosis vessels (p = 0.021). The lower VMS and VMSR, the higher possibility of severe coronary stenosis is. The VMS and VMSR lower than 13.9 ± 4.3 and 0.9 ± 0.3, respectively predicted the severe coronary stenosis. The VMS and VMSR higher than 16.9 ± 4.9 and 1.2 ± 0.3, respectively predicted mild or no coronary artery stenosis. Conclusions: The actual stenosis rate in catheterization demonstrates that this technique was able to assess coronary artery condition. Thus, the application of a non-invasive method of 2D-STE to evaluate and simplify diagnosis of CAD is feasible.